Characterization and ciprofloxacin adsorption properties of activated carbons prepared from biomass wastes by H3PO4 activation. (October 2016) - Sun, Yuanyuan; Li, Hong; Li, Guangci; Gao, Baoyu; Yue, Qinyan; Li, Xuebing
Highlights: Biomass wastes-derived activated carbon were prepared by one-step method. The properties of precursors were characterized by thermogravimetric analysis. The surface acidic functional groups were determined by NH3 -TPD. The characterization and adsorption properties of both carbons were compared. Abstract: As biomass wastes, Arundo donax Linn and pomelo peel were used as precursors for activated carbons (ALAC and PPAC) preparation by phosphoric acid activation. The pore structure and surface acidic functional groups of both carbons were characterized by nitrogen adsorption/desorption experiment, NH3 -temperature-programmed desorption (NH3 -TPD) and Fourier transform infrared spectroscopy (FTIR). A batch of experiments was carried out to investigate the adsorption performances of ciprofloxacin under different conditions. Results showed that PPAC exhibited larger surface area (1252 m 2 /g) and larger portion of mesoporous, while ALAC was typical of microporous materials. Results from NH3 -TPD suggested that ALAC was characteristic of more acidic functional group than PPAC. The maximum monolayer adsorption capability was 244 mg/g for ALAC and 400 mg/L for PPAC. Kinetics studies showed intra-particle diffusion was not the unique rate-controlling step. Boundary layer resistance existed between adsorbent and adsorbate.